Full genotyping and FAM19A4/miR124-2 methylation analysis in high-risk human papillomavirus–positive samples from women over 30 years participating in cervical cancer screening in Örebro, Sweden - Kaliff, Malin; Lillsunde Larsson, Gabriella; Helenius, Gisela; Karlsson, Mats G.; Bergengren, Lovisa (PloS one, 2022)
Currently, cervical cancer prevention is undergoing comprehensive development regarding human papillomavirus (HPV) vaccination and cervical cancer screening. In Sweden and many other countries, high coverage vaccinated cohorts are entering screening within the next few years. This entails demands for baseline HPV genotype data across the screening age range for surveillance and a basis for screening program adjustment. In 2016, Örebro County, Sweden, changed to primary HPV screening using HPV mRNA testing followed by cytology triage. An alternative triage method to cytology could allow for a fully molecular screening algorithm and be implemented in a screening program where self-sampling is included. Hypermethylation analysis of the human genes FAM19A4/miR124-2 has been suggested as a promising triage method. HPV mRNA-positive screening samples (n = 529) were included and subjected to genotyping targeting a broad range of both low-risk and high-risk genotypes in addition to hypermethylation analysis of the two human genes FAM19A4/miR124-2. Data were connected to cytological and histological status and age. The most commonly detected genotypes were HPV31, 16, and 52. In addition, HPV18 was one of the most common genotypes in high-grade squamous intraepithelial lesions (HSILs) samples. In relation to available vaccines, 26% of the women with histological HSIL or cancer (≥HSIL) tested positive for only hrHPV included in the quadrivalent vaccine and 77% of the genotypes in the nonavalent vaccine. According to these figures, a relatively large proportion of the HSILs will probably remain, even after age cohorts vaccinated with the quadrivalent vaccine enter the screening program. Hypermethylation positivity was associated with increasing age, but no HPV-related independently predictive factors were found. Accordingly, age needs to be considered in development of future screening algorithms including triage with hypermethylation methodology.